2021
DOI: 10.1371/journal.pone.0256847
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of late detection and advanced-stage diagnosis of breast cancer in Nigeria

Abstract: Late detection of Breast cancer(BC) and progressing with advanced-stage diagnosis after early detection contribute differently to the challenges of managing BC in Africa. Understanding the difference may improve cancer education programs and their effectiveness. Objective To describe the risk factors for late detection and advanced-stage diagnosis among patients who detected their BC early. Method Using secondary data, we analyzed the impact of socio-demographic factors, premorbid experience, BC knowledge, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…20 Increased knowledge of risk factors, symptoms/signs, and screening methods of BC will lead to early BC diagnosis and management and a high survival rate. 21 The present study showed poor BC knowledge among respondents in general. The results of the survey showed that there is a small proportion of respondents (22.09%) with good knowledge on the set of items evaluated, including knowledge of signs/symptoms, risk factors, and screening methods of BC.…”
Section: Discussionmentioning
confidence: 47%
See 2 more Smart Citations
“…20 Increased knowledge of risk factors, symptoms/signs, and screening methods of BC will lead to early BC diagnosis and management and a high survival rate. 21 The present study showed poor BC knowledge among respondents in general. The results of the survey showed that there is a small proportion of respondents (22.09%) with good knowledge on the set of items evaluated, including knowledge of signs/symptoms, risk factors, and screening methods of BC.…”
Section: Discussionmentioning
confidence: 47%
“… 20 Increased knowledge of risk factors, symptoms/signs, and screening methods of BC will lead to early BC diagnosis and management and a high survival rate. 21 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education inequalities were significantly associated with rate of BCS performance, diagnostic journey, and stage of BC diagnosis. Several studies claimed that highly educated individuals were more likely to practice BCS, have shorter delay, and were less likely to present at advanced stages compared to those with low educational level (5,8,14,15,17–20,22,28,29,3133,36,40,44,49,51). This could be explained by the fact that individuals with low educational level are less likely to be offered good paying jobs; subsequently, they cannot afford access to healthcare.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other three studies with much less sample sizes (one in Thailand, one in Colombia and one in Korea) concluded that older patients had higher odds of getting diagnosed at late stages compared to younger patients (3638). Moreover, four other studies that have been conducted in three African countries (two in Nigeria, one in South Africa, and one in Ethiopia) concluded that age was not significantly associated with advanced stage diagnosis of BC (4,5,39,40).…”
Section: Methodsmentioning
confidence: 97%